Commercially and economically important fish species from an otter trawling vessel of Bay of Bengal, Bangladesh - Sunny, Saif Khan; Firdaws, Syeda Jasia; Zaman, Maria; Alam, Md Masud Ul Alam (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The study was conducted on the commercially and economically important fish species in the Bay of Bengal (BoB) that were collected from an otter trawling vessel in March 2020. Within the study period, a total of 52 species were identified, including 17 orders, and 43 families. Perciformes were found to be the most dominant order over all others, contributing about 46.15% of the fish species (24 species under 23 families). A record of catching immature species has been found, which can reduce the sustainability of fisheries. We have found one critically endangered (CR), two near threatened (NT), twenty-five least concerned (LC), four data deficient (DD), and twenty not evaluated (NE) species among the fifty-two species in the BoB during the study period. Many commercially important fish species within the bay need to be exploited properly to get maximum economic benefits. J. Asiat. Soc. Bangladesh, Sci. 49(1): 13-25, June 2023